Strengthening collaborative governance in preventive and sustainable flood disaster management - Muhammad Adnan Al Kadly Kanedy (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The present scholarly inquiry examines collaborative governance in flood disaster management in Bengkulu Province, Indonesia, where recurrent hydrometeorological floods generate multidimensional consequences for communities, public services, infrastructure, health, livelihoods, and the environment. Rather than treating floods solely as natural hazards, the inquiry positions flood management as a governance challenge that requires coordinated action across institutions, sectors, and levels of society. Methods: Using a qualitative approach based on document analysis, the research draws on policy documents, regulations, government reports, National Agency for Disaster Counterm National Agency for Disaster Counterm and Regional Agency for Disaster Management publications, media coverage, and relevant scholarly articles. The analysis is guided by Ansell and Gash’s collaborative governance framework, with attention to starting conditions, institutional design, facilitative leadership, and collaborative processes. Findings: The findings indicate that collaborative practices have begun to emerge in Bengkulu’s flood management, particularly during emergency response. Local governments, Regional Agency for Disaster Management, regional apparatus organizations, sub-district and village officials, volunteers, community groups, media actors, and other stakeholders participate in rapid assessment, evacuation, logistical distribution, temporary shelters, evacuation tents, and mobile public kitchens. However, collaboration remains predominantly reactive, operational, and incident-based. Preventive collaboration in mitigation, preparedness, risk reduction, and post-disaster recovery is still limited by uneven institutional capacity, fragmented information systems, overlapping roles, and weak community involvement in decision-making. Conclusion: The article argues that flood governance in Bengkulu must move from reactive coordination toward preventive, adaptive, and sustainable collaboration involving government agencies, technical institutions, volunteers, media, and communities, while embedding disaster risk reduction into regional development planning systems. Novelty/Originality of this article: The novelty of this inquiry lies in its governance-oriented reading of flood management in Bengkulu, which links recurring flood impacts with the maturity of collaborative governance arrangements rather than merely describing emergency response activities.